Characteristics of turbulent forced convective nanofluid flow and heat transfer in a 2D axisymmetric corrugated pipe. (1st June 2023) - Shuvo, Md. Shahneoug; Ruvo, Tahmidul Haque; Saha, Sumon
Graphical abstract: Highlights: Turbulent forced convective nanofluid flow in an axisymmetric corrugated pipe is studied. Effects of geometric and governing parameters on thermo-fluid performance are investigated. Based on the thermal performance analysis, critical corrugation height, h  = 0.03181 D is found. Highest thermal efficiency is observed at h  = 0.03181 D, Reτ  = 314, fc  = 18, and φ  = 2%. Abstract: A computational investigation using a single-phase model has been carried out for a turbulent forced convective nanofluid flow composed of water and Al 2 O 3 nanoparticles through a horizontal corrugated pipe. A uniform heat flux boundary condition is imposed on the corrugated pipe wall. The Reynolds-Averaged Navier-Stokes and energy equations, along with Shear Stress Transport turbulence model, are solved utilizing the finite element technique. Parametric simulations are conducted by varying corrugation heights (0 ≤  h  ≤ 0.07952 D, where D is the mean diameter of the pipe), Kármán number ( Reτ  = 180, 250, 314), corrugation frequency ( fc  = 12, 15, 18), the volume percentage of nanoparticles (0 ≤  φ  ≤ 0.02). Normalized mean velocity, mean temperature, radial heat flux, and Reynolds shear stress profiles are plotted to show the effects of governing parameters. Besides, the resemblance in average Nusselt number and friction factor are presented. To grasp the effectiveness of heat transfer, thermal efficiency has been calculated to find the optimum condition, and it reveals that the critical corrugation height, h  = 0.0318 D at Reτ  = 314, fc  = 18, φ  = 2% corresponds to higher thermal efficiency.